Chlorine Adsorption Characteristics of NaX, NaY and Mordenite Zeolites - Xue, Jian-Wei; Zhao, Hui-Ling; Wang, Hui; Li, Fu-Xiang; Lv, Zhi-Ping (Asian Journal of Chemistry, 2012)
This paper examines the potential of zeolites as ideal chlorine adsorption materials. The NaX, NaY and mordenite zeolites, a large class of highly crystalline aluminosilicate materials that encompass well-defined channels and cavities, were investigated and compared according to their chlorine adsorption properties. The chlorine adsorption capacities were measured by a pressure-composition-temperature experimental setup and the data were obtained at a temperature range of 273-323 K and pressures in the range of 0-0.35 MPa. At 273 K and 0.317 MPa, the maximum adsorption capacity was 29.02 % for the NaY zeolite, 28.96 % for the mordenite zeolite and 21.03 % for the NaX zeolite. The experimental data show that the chlorine uptakes in the zeolites are strongly dependent on temperature and pressure, as well as on the framework and aperture type.